Stakeholder efforts to mitigate antiretroviral therapy interruption among people living with HIV during the COVID‐19 pandemic in China: a qualitative study. Issue 9 (2nd September 2021) - Sun, Yinghui; Zhan, Yuewei; Li, Hui; Yuan, Tanwei; Gao, Yanxiao; Liang, Bowen; Feng, Anping; Li, Peiyang; Zheng, Weiran; Fitzpatrick, Thomas; Wu, Dan; Zhai, Xinyi; et al.
Abstract: Introduction: The COVID‐19 pandemic has affected antiretroviral therapy (ART) continuity among people living with HIV (PLHIV) worldwide. We conducted a qualitative study to explore barriers to ART maintenance and solutions to ART interruption when stringent COVID‐19 control measures were implemented in China, from the perspective of PLHIV and relevant key stakeholders. Methods: Between 11 February and 15 February 2020, we interviewed PLHIV, community‐based organization (CBO) workers, staff from centres for disease control and prevention (CDC) at various levels whose work is relevant to HIV care (CDC staff), HIV doctors and nurses and drug vendors from various regions in China. Semi‐structured interviews were conducted using a messaging and social media app. Challenges and responses relevant to ART continuity during the COVID‐19 pandemic were discussed. Themes were identified by transcript coding and mindmaps. Results: Sixty‐four stakeholders were recruited, including 16 PLHIV, 17 CBO workers, 15 CDC staff, 14 HIV doctors and nurses and two drug vendors. Many CDC staff, HIV doctors and nurses responsible for ART delivery and HIV care were shifted to COVID‐19 response efforts. Barriers to ART maintenance were (a) travel restrictions, (b) inadequate communication and bureaucratic obstacles, (c) shortage in personnel, (d) privacy concerns, and (e) insufficient ART reserve. CBO helped PLHIV maintain access to ART through five solutions identified from thematic analysis: (a) coordination to refill ART from local CDC clinics or hospitals, (b) delivery of ART by mail, (c) privacy protection measures, (d) mental health counselling, and (e) providing connections to alternative sources of ART. Drug vendors contributed to ART maintenance by selling out‐of‐pocket ART. Conclusions: Social and institutional disruption from COVID‐19 contributed to increased risk of ART interruption among PLHIV in China. Collaboration among key stakeholders was needed to maintain access to ART, with CBO playing an important role. Other countries facing ART interruption during current or future public health emergencies may learn from the solutions employed in China.